2008
DOI: 10.1029/2007tc002197
|View full text |Cite
|
Sign up to set email alerts
|

Recent extension driven by mantle upwelling beneath the Admiralty Mountains (East Antarctica)

Abstract: Northern Victoria Land is located at the boundary between an extended, presumably hot, region (West Antarctic Rift System) and the thick, possibly cold, East Antarctic craton. The style and timing of Tertiary deformation along with relationships with the magmatic activity are still unclear, and contrasting models have been proposed. We performed structural and morphotectonic analyses at the NE termination of northern Victoria Land in the Admiralty Mountains area, where the relationship between topography, tect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 73 publications
1
36
1
Order By: Relevance
“…The tilted blocks comprise an en echelon structural array with an overall NE-SW direction that starts south of the Adare Trough and approaches Cape Adare. Faulting reached the shelf edge, indicating that this event was probably linked with rifting activity outside the basin (most likely with the east dipping faulting in the northern Victoria Land [Faccenna et al, 2008]). [53] No motion is observed in the VLB during this interval [Fielding et al, 2008], as expected given its proximity to the Eocene-Oligocene pole of rotation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The tilted blocks comprise an en echelon structural array with an overall NE-SW direction that starts south of the Adare Trough and approaches Cape Adare. Faulting reached the shelf edge, indicating that this event was probably linked with rifting activity outside the basin (most likely with the east dipping faulting in the northern Victoria Land [Faccenna et al, 2008]). [53] No motion is observed in the VLB during this interval [Fielding et al, 2008], as expected given its proximity to the Eocene-Oligocene pole of rotation.…”
Section: Discussionmentioning
confidence: 99%
“…A pronounced extensional phase is also evident in the Admiralty Mountains Block, located immediately southwest of the Adare Basin (Figure 1) [Faccenna et al, 2008]. There, a total of 5 km of extension was accommodated along a set of NE-SW to N-S trending normal faults since the middle Miocene [Faccenna et al, 2008]. Further south, LeMasurier [2008] has suggested that subice deep troughs and basins filled with thin layers of sediments (Figure 1) [Anandakrishnan and Winberry, 2004] were formed underneath the Ross Ice Shelf and West Antarctic ice sheet during the Neogene.…”
Section: Tectonic Setting and History Of The West Antarctic Rift Systemmentioning
confidence: 96%
See 3 more Smart Citations